Module Over Pseudo-Valuation Ring and Domain (European Journal of Pure and Applied Mathematics, 2017)
Modules over principal ideal rings, dedekind rings and valuation rings have been discussed in the literature. In this article, we introduce and discuss the module over pseudo-valuation ring(PVR) and its submodule. Also as a byproduct we introduce the module over pseudo-valuation domain(PVD).